Population structure and dynamic characteristics of three endemic Chinese Abies species in southeastern Tibet, China - Di Huang; Di Huang; Di Huang; Di Huang; Di Huang; Yihua Ren; Yihua Ren; Yihua Ren; Yihua Ren; Yihua Ren; Shouzhi Yang; Shouzhi Yang; et al. (Frontiers in Ecology and Evolution)
IntroductionIn the face of escalating climate change, conserving fir forests in southeastern Tibet is paramount. These forests uphold Tibetan biodiversity and support crucial ecological services.MethodsThis study used the typical plot method to investigate the survival status and development trends of three Chinese endemic Abies species, namely, Abies georgei var. smithii, Abies chayuensis, and Abies delavayi var. motuoensis, from the diameter structure, static life table, and survival curve.ResultsThe results revealed that 1) the density of Abies georgei var. smithii, Abies chayuensis, and Abies delavayi var. motuoensis in the community is 408, 320, and 103 trees per hectare, respectively. The structure of the diameter class of the three species of fir trees is a pyramid shape. As the diameter class increases, the number of each population fluctuates to varying degrees, and there is a lack of many medium- and large-diameter trees. 2) The survival curve of Abies georgei var. smithii tends to be similar to the Deevey type II curves, whereas the survival curves of Abies chayuensis and Abies delavayi var. motuoensis tend to be similar to the Deevey type III curves. Various population structures are growth-oriented but highly sensitive to external random disturbances, with mortality and disappearance rates multiple times, indicating poor population development. Survival analysis reveals that all populations begin to decline after the middle age range and that the age structure is relatively unstable.DiscussionThe results of this study contribute to revealing the structural characteristics and dynamic patterns of various spruce populations, providing a theoretical basis for the management and sustainable utilization of fir forests in southeastern Tibet.